The complex treatments efficiency of the patients with vertebrogennoy thoracalgy - V S Goidenko; I L Fedorova (RUDN Journal of Medicine, 2010)
In article the estimation of the complex treatments efficiency including manual therapy and reflexotherapy of the patients with vertebrogennoy thoracalgy. This is allows to increase antinociceptive effect of the basic mechanisms regulation nociceptive of sensitivity.